2022
DOI: 10.1093/fampra/cmac057
|View full text |Cite
|
Sign up to set email alerts
|

The use of antibiotics in acute oral health patients presenting at public dental clinics in the Western Sydney region

Abstract: Background There is a limited need for antibiotics when treating oral health problems, yet they are often prescribed, increasing risk of antimicrobial resistance (AMR). With AMR a threat to public health, the objectives of this study were to assess the frequency, suitability, and factors associated with antibiotic prescriptions for acute dental problems across Greater Western Sydney public dental clinics. Methods Patients’ re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In general, they are only needed when a tooth infection shows signs of systemic spread (Therapeutic Guidelines 2019). However, multiple studies have shown that GPs tend to prescribe antibiotics as treatment for dental conditions (Anderson et al 2000;Cope et al 2015;Nguyen et al 2023). An Australian case-vignette study of 30 GPs who worked in rural Queensland, Tasmania and South Australia between 2013 and 2014 showed that GPs tend to prescribe antibiotics and short-term pain relief for dental conditions, including toothaches, dental abscesses and acute orofacial pain (Park et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In general, they are only needed when a tooth infection shows signs of systemic spread (Therapeutic Guidelines 2019). However, multiple studies have shown that GPs tend to prescribe antibiotics as treatment for dental conditions (Anderson et al 2000;Cope et al 2015;Nguyen et al 2023). An Australian case-vignette study of 30 GPs who worked in rural Queensland, Tasmania and South Australia between 2013 and 2014 showed that GPs tend to prescribe antibiotics and short-term pain relief for dental conditions, including toothaches, dental abscesses and acute orofacial pain (Park et al 2022).…”
Section: Introductionmentioning
confidence: 99%